Navigating the Future: Human Rights Implications of Artificial Intelligence - Marsili, M. (Beyond Europe: Artificial Intelligence. Artificial Intelligence in International Relations and Communications. Opportunities and Challenges, 2024)
The rise of artificial intelligence (AI) poses unprecedented challenges to human rights, as its integration into political, health, and communication sectors introduces significant risks to individual autonomy, privacy, and mental integrity. This paper critically examines the potential implications of AI on human rights, highlighting the ethical dilemmas and regulatory gaps associated with its application across various societal domains. With AI's ability to influence behavior, process sensitive data, and operate autonomously, the urgent need for robust ethical frameworks and international governance has never been clearer. This study explores strategies to safeguard against the threats posed by AI in digital and cognitive domains, underscoring the impact of AI-driven surveillance, manipulation, and algorithmic decision-making on fundamental rights. It investigates how current human rights protections may fall short in the face of rapid technological advancements, leading to new forms of discrimination and oppression. Drawing from research in cognitive warfare and cybersecurity, the analysis proposes the establishment of new human rights protections tailored to address AI's role in shaping mental and behavioral domains. It emphasizes the critical importance of rights to cognitive liberty, mental privacy, and informational autonomy. Additionally, it examines the role of AI in perpetuating dehumanizing processes and the imperative need for safeguards that prioritize human dignity and psychological well-being. The study further suggests that developing ethical and legal standards is crucial to preventing AI misuse. It advocates for a multidisciplinary approach that brings together insights from technology, law, and human rights advocacy. The proposed recommendations include the creation of clear guidelines for AI usage, transparency in AI systems, and mechanisms for accountability in cases of rights violations. As AI’s influence on society continues to grow, a proactive and protective approach to human rights becomes essential to responsibly navigate the societal impacts of these technologies. By contributing to ongoing discussions about the risks AI poses to human rights, this paper calls for a balanced, globally-coordinated regulatory approach that aligns with the ethical and social demands of the AI era. Ultimately, safeguarding human rights in the age of AI is not merely a technological challenge but a moral imperative that requires collective action and commitment from all stakeholders.